Effects of treadmill exercises on pancreatic β cell function through the role of vitamin D in patients with type 2 diabetes mellitus. - Irawati, Anugrahini; Mudjanarko, Sony Wibisono; Tinduh, Damayanti (Gaceta Médica de Caracas, 2021)
Background: Vitamin D is a lipophilic compound that can be trapped in adipose tissue that is often obtained in metabolic syndrome. This study aims to compare 25(OH)D levels and pancreatic β cell function before and after moderate-intensity treadmill with increased speed and gradual inclination in type 2 diabetic patients.